Evaluation of crack propagation and fatigue strength of rib-to-deck welds based on effective notch stress method. (20th March 2019) - Wang, Qiudong; Ji, Bohai; Fu, Zhongqiu; Ye, Zhi
Graphical abstract: Highlights: The effective notch stress approach is adopted. The experimental and numerical crack propagating paths were compared. A simplified simulation method for a fatigue test is proposed. The reasonability of recommended notch stress-based S-N curves is evaluated. Abstract: The fatigue data of tested specimens was referred to, and an additional three specimens were tested to obtain the crack section. The stress distribution, crack initiation position, and crack propagation path were compared with the effective notch-based numerical results. A simplified simulation of the fatigue test, considering the effect of welding residual stress, was also performed. The fatigue lives of tested specimens, as well as numerical results, were investigated in the effective notch stress system to investigate the feasibility of the effective notch stress approach. The results show that the effective notch stress approach is precise enough to determine the crack propagation path. The proposed simulation method for fatigue testing is demonstrated to be feasible when predicting the fatigue life, and the SWT parameter is found with higher accuracy by taking into consideration the welding residual stress. It is reasonable to assess the fatigue strength of rib-to-deck welds by the classification of FAT-225 recommended by IIW using an effective notch stress approach.